Effect of processing parameters on microstructure of laser melted titanium alloys - Abdul Hafiz Abdul Rahman (2017)
Selective laser melting (SLM) is one of the additive manufacturing (AM) processes that produces complicated parts by fusing metallic powders with a high-energy beam from computer-aided design (CAD) data. With the involvement of numerous processing parameters, SLM may influence the properties of the final part. Application of inappropriate processing conditions may result in multiple defects like balling, cracks and irregularities in the surface morphology. Hence, establishing the relationship between the processing parameters by SLM and surface morphology is important to produce a fully density parts. In this study, equal weight percentages of titanium and tantalum powder (Ti-50%wt Ta) was fabricated using SLM. The influence of processing parameters on the microstructure and other properties like relative density, microhardness and surface roughness were investigated. The results show that a fully dense titanium-tantalum part able to obtain a high microhardness value in both xy-plane and yz-plane with a minimum surface roughness value in xy-plane. The relative density achieved by Archimedes method is close to 99.9 %. TiTa shows laminar β grains in the random direction in both xy and yz-plane from optical microscope (OM) analysis. This measurement is further confirmed using X-ray diffraction (XRD) which indicate the presence of β phase, which consist of body centered cubic (BCC) structure. Throughout the SLM process, the titanium powder able to melt entirely due to the adequate amount of energy density applied but because of tantalum high melting point, several large tantalum particles melted partially.